Ex vivo γH2AX radiation sensitivity assay in prostate cancer: Inter-patient and intra-patient heterogeneity. Issue 3 (September 2017) - De-Colle, Chiara; Yaromina, Ala; Hennenlotter, Joerg; Thames, Howard; Mueller, Arndt-Christian; Neumann, Tim; Stenzl, Arnulf; Scharpf, Marcus; Fend, Falko; Ricardi, Umberto; Baumann, Michael; Zips, Daniel; et al.
Abstract: Introduction: The aim of the study is to assess inter-patient and intra-patient heterogeneity in tumour cell radiosensitivity using the ex vivo γH2AX assay in prostate cancer specimens. Methods: Excised specimens from untreated prostate cancer patients were cultivated 24 h in media, irradiated ex vivo and fixed after 24 h. Residual γH2AX foci were counted and the slope of the dose response was calculated. Intra-patient heterogeneity was studied from three to seven different biopsies. Results: In pathology-confirmed tumour samples from 21 patients the slope of residual γH2AX foci and radiation dose showed a substantial heterogeneity ranging from 0.82 to 3.17 foci/Gy. No correlation was observed between the slope values and the Gleason score ( p  = 0.37), prostate specific antigen ( p  = 0.48) and tumour stage ( p  = 0.89). ANOVA indicated that only in 1 out of 9 patients, biopsies from different tumour locations yielded statistically significant differences. Variance component analysis indicated higher inter-patient than intra-patient variability. Bootstrap simulation study demonstrated that one biopsy is sufficient to estimate the mean value of residual γH2AX per dose level and account for intra-patient heterogeneity. Conclusions: In prostate cancer inter-patient heterogeneity in tumour cell radiation sensitivity is pronounced and higher than intra-patient heterogeneity supporting the further development of the γH2AX ex vivo assay as a biomarker for individualized treatment.